Exploring the Career Motivations, Strengths, and Challenges of Autistic and Non-autistic University Students: Insights From a Participatory Study - Cheriyan, Chinnu; Shevchuk-Hill, Sergey; Riccio, Ariana; Vincent, Jonathan; Kapp, Steven K.; Cage, Eilidh; Dwyer, Patrick; Kofner, Bella; Attwood, Helen; Gillespie-Lynch, Kristen (Frontiers in Psychology, 2021)
Supports for the growing number of autistic university students often focus on helping them succeed in university. However, even educated autistic people experience discrimination and other challenges which can make it very difficult for them to obtain meaningful jobs. Little remains known about how universities can better support their autistic students and alumni in overcoming barriers to meaningful employment. In this participatory study, a team of autistic and non-autistic researchers asked autistic (n = 92) and non-autistic (n = 774) university students about their career aspirations, strengths they believe will help them succeed in their “dream jobs”, and obstacles they expect to encounter. Autistic participants’ top goal in attending college was to improve their career prospects. However, relatively few autistic students reported learning career-specific skills at university. Autistic students were more likely to seek an academic job and less likely to seek a career in healthcare than non-autistic students. Autistic students highlighted writing skills and detail orientation as strengths that could help them succeed in their dream jobs more often than non-autistic students. However, they were also more likely to expect discrimination, social, and psychological difficulties to stand in the way of their dream jobs. These findings suggest that universities should prioritize experiential learning opportunities to help autistic (and non-autistic) students develop employment-related skills while providing mental health supports. Universities should demonstrate their commitment to supporting diverse learners by seeking out and hiring autistic professionals and by teaching their own staff and employers how to appreciate and support autistic colleagues.